The Appearance of New Active Forms of Trypsin Inhibitor in Germinating Mung Bean (Vigna radiata) Seeds - Lorensen, Elke (1981)
Ungerminated seeds of mung bean contain a single major species (F) of trypsin inhibitor with five minor species (A-E) separable on diethylaminoethyl-cellulose. During germination the level of trypsin inhibitory activity decreases from 1.8 units/grams dry weight in ungerminated cotyledons to 1.2 units/grams in cotyledons from seeds germinated 5 days. This decrease is accompanied by major changes in the distribution of inhibitory activity among the inhibitor species. By 48 hours of germination, inhibitor F has largely disappeared with an accompanying rapid increase in inhibitor C. Similarly, though less rapidly, inhibitor E decreases while inhibitor A increases. A similar sequence of changes is found in vitro when purified inhibitor F is incubated with extracts from seeds germinated 96 hours. The combined in vivo and in vitro data suggest a conversion sequence of: F → E → C → A. The in vitro conversion is inhibited by phenylmethyl sulfonyl fluoride but not by iodoacetamide, indicating that at least the initial phases of inhibitor conversion are not catalyzed by the mung bean vicilin peptidohydrolase.